2020
DOI: 10.1002/ejoc.201901793
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Induced Metal‐Free Trifluoromethylselenolation of Electron‐Rich Heteroarenes Using the Nucleophilic [Me4N][SeCF3] Reagent

Abstract: A metal-free visible-light-promoted regioselective trifluoromethylselenolation of electron-rich heteroarenes has been developed using C-H functionalization. This eco-friendly, atom-economical, and easy-to-operate protocol provides direct [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…A control reaction, without Pd catalyst (Table 2; entry 18), confirmed that the process required a metal catalysis. During our investigations to determine the optimal conditions, the formation of CF 3 SeSeCF 3 dimer was regularly highlighted by 19 F NMR. In order to determine the origin of this dimer, the behavior of 1 a in DMSO at 70°C was monitored by 19 F NMR (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…A control reaction, without Pd catalyst (Table 2; entry 18), confirmed that the process required a metal catalysis. During our investigations to determine the optimal conditions, the formation of CF 3 SeSeCF 3 dimer was regularly highlighted by 19 F NMR. In order to determine the origin of this dimer, the behavior of 1 a in DMSO at 70°C was monitored by 19 F NMR (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…In view of these results, Pd[CH 3 CN] 2 Cl 2 (20 mol %), without pivalic acid, under air, at 70°C for 24 h (entry 13) was selected as optimal conditions, the best yields being obtained in this case. CuBr [b] OMe 0/9 6 CuBr [c] OMe 8/15 [d] [a] Yields determined by 19 F NMR with PhOCF 3 as internal standard, reported to 2 a or 3 a. Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also conducted this reaction with continuous flow techniques (Scheme 21). [42] Unfortunately, this reaction is limited to electron‐rich heteroarenes. A radical mechanism was supported by EPR experiments.…”
Section: Nucleophilic Trifluoromethylselenolation Reagentsmentioning
confidence: 99%